Detection and recovery of hydrolytic enzymes from spent compost of four mushroom species - Ko, Han Gyu; Park, Sang Ho; Kim, Seong Hwan; Park, Hyuk Gu; Park, Won Mok (Folia microbiologica, 2005)
To evaluate the potential of using the enzymes from spent mushroom compost (SMC) as an industrial enzyme, the production of alpha-amylase, cellulase, beta-glucosidase, laccase, and xylanase was determined from the SMC of four edible mushroom species (Pleurotus ostreatus, Lentinula edodes, Flammulina velutipes and Hericium erinaceum). Among the tested SMC, the SMC of L. edodes showed the highest enzyme activity in alpha-amylase (229 nkat/g), cellulase (759 nkat/g) and beta-glucosidase (767 nkat/g) in 0.5% Triton X-100, and that of P. ostreatus showed the highest activity in laccase (1452 nkat/g) in phosphate-buffered 0.2% Triton X-100. The highest xylanase activity (119 nkat/g) was found in the SMC of F. velutipes.
Keywords: Laccase; Cellulase; Shiitake Mushrooms; Biodegradation, Environmental; biodegradace; Hydrolases; Endo-1,4-beta Xylanases; alpha-Amylases; endo-1,4-beta-xylanasy; Basidiomycota; hydrolasy; celulasa; houby šii-take; alfa-amylasy; beta-glukosidasa; beta-Glucosidase; Pleurotus; lakasa